2017
DOI: 10.1021/acs.jpcc.7b09108
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Acid-Conjugated Gold Clusters: Interaction of Alanine and Tryptophan with Au8 and Au20

Abstract: The stability and electronic properties of gold (Au) clusters interacting with the amino acids alanine (Ala) and tryptophan (Trp) in their canonical and zwitterionic configurations were investigated using first-principles density functional theory (DFT). We found that the geometrical structures of the Au clusters and the polarities of the amino acids determine the nature of the interactions in the gas and solvent phases. In the gas phase, the Au8 (D 4h ) and Au20 (T d ) clusters prefer single-site interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 86 publications
(116 reference statements)
3
16
0
Order By: Relevance
“…The authors found that canonical amino acids preferred single site interactions through an amine group, while in their zw form, amino acids interact through a carboxylic site (COOH). Our finding about the binding of zw forms of Glycine and Alanine to Au n cluster through their COOH end ( Figure 1) is in congruence with the results of Abdalmoneam et al [59] Positive BE 1 (see Table 2) entails the stability of Glycine/Alanine-Au n complexes. [56,59] There are numerous reports on the anchoring of a single amino acid to gold clusters.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The authors found that canonical amino acids preferred single site interactions through an amine group, while in their zw form, amino acids interact through a carboxylic site (COOH). Our finding about the binding of zw forms of Glycine and Alanine to Au n cluster through their COOH end ( Figure 1) is in congruence with the results of Abdalmoneam et al [59] Positive BE 1 (see Table 2) entails the stability of Glycine/Alanine-Au n complexes. [56,59] There are numerous reports on the anchoring of a single amino acid to gold clusters.…”
Section: Resultssupporting
confidence: 92%
“…Our finding about the binding of zw forms of Glycine and Alanine to Au n cluster through their COOH end ( Figure 1) is in congruence with the results of Abdalmoneam et al [59] Positive BE 1 (see Table 2) entails the stability of Glycine/Alanine-Au n complexes. [56,59] There are numerous reports on the anchoring of a single amino acid to gold clusters. However, the interaction of dipeptides with metallic surfaces or clusters has been explored only to a limited extent.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations